Analysis Factor that Related to the Nurse in Gives Personal Hygiene to Total Care - Klau, Oktovianus Tahu; Wahyudi, Andri Setiya; Pradanie, Retnayu (Fundamental and Management Nursing Journal, 2020)
Introduction: The requirement of client personal hygiene is done by nurse. Nurse motivation is saturated by personal hygiene being regarded by intrinsik and ekstrinsik motivation. The purpose of this research is: Analysis factor that related to the Nurse in gives personal hygiene to total care.Method: Desain Cross Sectional. Observational population: Executer nirse at 9 room nurse to lodge adults in Regions Common Hospital prof. Dr.W.Z. Yohanesz Kupang. Sample: 106 respondents that accomplish inclusi's criterion. Dependen's variable: Motivation. Independen's variable: responsibility, pay, working conditio, safety of working and co- worker and superior relationship. Data collecting utulizes closed quesioner and Analysis with logistic regression.Results:  There are relationship among two factors with logistic regresson which is Responsibility factor (p= 0,000), and  Co- worker superior relationship with point (p= 0,025). Severally factor which repudiated is Pay (p= 0,275) working conditio (p= 0,951) and Safety of working (p= 0,999).Conclusion: Nurse motivation is related to the responsibility factor and Co- Worker and superior relationship. Need again been analyzed succes factor solved task, appreciation and the job itself. Pretty much chance amends goes forward hospital procedure, state, and technics supervisory.